O potrzebie zmian w polskim prawie rozwodowym: [On the need for change in Polish divorce law] (Studia Prawnicze / The Legal Studies, 2016)
Zmiany prawa wynikają w swej najgłębszej warstwie z przemian rzeczywistości, której dany akt prawny dotyczy, w tym jej aspektów politycznych, technologicznych, demograficznych, ekonomicznych, obyczajowych, moralnych i innych. Bywa, że nowe regulacje prawne odzwierciedlają pojawienie się takich czy innych prądów myślowych lub zachowań, na które ustawodawca reaguje (pozytywnie lub karcąco) albo też zamierza je wykreować. Modyfikacje uregulowań prawnych zawsze wymagają rozwagi, roztropności, respektu dla skomplikowanej materii, wszechstronnej o niej wiedzy, a jeśli dotyczą one rzeczywistości tak złożonej i delikatnej jak rodzina, wówczas argumenty za ich przeprowadzaniem muszą być szczególnie mocne. The author discusses an always relevant problem of the model of the procedure for dissolving marriage. The problem is analyzed from the point of view not only of law, but also social sciences, primarily, psychology. He observes a presence of a dominant tendency nowadays to deemphasize the meaning of marriage and family, and to succumb to crisis and file for a divorce for banal reasons. The so called pro-divorce mentality translates into a tendency observed among judges to favour divorce. On the other hand, the author assesses the legal acts referring to divorce cases as reasonable, i.e. neither favoring nor facilitating divorce. Therefore, a need is emphasized to change the approach to the family in a critical situation. He suggests that in a family court instead of settling family legal problems an attempt should be made to solve them. To this effect, in local communities, special groups comprising psychologists, pedagogues, lawyers, social workers and other specialists should be set up. The ultimate goal for the groups would be to try to reconcile the spouses, to help them solve their family problems, including assistance in dealing with all divorce procedures. People dissatisfied with the proposal suggested by such a group might have a right to file a case in court. In court the proceedings should be held in compliance not with the so far applied adversarial principle but with the conciliatory principle.